2021
DOI: 10.3390/nu13113826
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Intake of Dietary Fibre in Adolescents, Adults, and Elderlies: Results of Slovenian Representative SI. Menu Study

Abstract: Dietary fibre has proven to promote healthy body mass and reduce the risk of non-communicable diseases. To date, in Slovenia, there were only a few outdated studies of dietary fibre intake; therefore, we explored the dietary fibre intake using food consumption data collected in the SI.Menu project. Following the EU Menu methodology, data were collected on representative samples of adolescents, adults, and elderlies using a general questionnaire, a food propensity questionnaire, and two 24 h recalls. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
(58 reference statements)
3
22
0
2
Order By: Relevance
“…The Slovenian national dietary survey SI.Menu was conducted in 2017/2018 ( 104 ), and the 2017 edition of the branded foods dataset was used to estimate the nutritional composition of reported foods. This approach has already supported several epidemiological studies, which investigated diet-related-risk factors and population intakes of total/free sugars ( 69 ), dietary fiber ( 70 ), TFAs ( 68 ), vitamin D ( 67 ) and folate ( 71 ).…”
Section: The Exploitation Of Use Of Branded Foods Database In Nutrition Researchmentioning
confidence: 97%
“…The Slovenian national dietary survey SI.Menu was conducted in 2017/2018 ( 104 ), and the 2017 edition of the branded foods dataset was used to estimate the nutritional composition of reported foods. This approach has already supported several epidemiological studies, which investigated diet-related-risk factors and population intakes of total/free sugars ( 69 ), dietary fiber ( 70 ), TFAs ( 68 ), vitamin D ( 67 ) and folate ( 71 ).…”
Section: The Exploitation Of Use Of Branded Foods Database In Nutrition Researchmentioning
confidence: 97%
“…The most recent data in a Slovenian report (e.g., national cross-sectional food survey, SI. Menu, that collected food consumption data in the period from March 2017 to April 2018 [54]) showed that 22% of adolescents, 39% of adults and 43% of older adults were overweight, and a similar proportion was observed in the obese class (6% of adolescents, 20% of adults and 32% of older adults). These numbers are in line with the assessed average body fat percentage (BF %) (measured by bioimpedance) for adult and older females (33% and 37%) as well as for adult and older males (25% and 29%) [55].…”
Section: Body Mass and Body Compositionmentioning
confidence: 99%
“…The most recent data in a Slovenian report (e.g., national cross-sectional food survey, SI. Menu, that collected food consumption data in the period from March 2017 to April 2018 [54]) showed that 22% of adolescents, 39% of adults and 43% of older adults were overweight, and a similar proportion was observed in the obese class (6% of adolescents,…”
Section: Body Mass and Body Compositionmentioning
confidence: 99%
“…Omega-3-fatty acids offer protection against a number of pathologies such as diabetes, cardiovascular events (arrhythmias, recurrent myocardial infarction, and cardiac death), and cognitive decline. A study conducted by Seljak et al (2021) revealed that around 83.9% of the elderly population in Slovenia are living with inadequate dietary fiber intake (<30 g/day) (Seljak et al, 2021) while another study showed 90.1% of seniors (≥60 years old) in Brazil are living with inadequate dietary fiber intake (Silva et al, 2019). A considerable percentage of US adults (including elder population) do not meet the recommended levels of omega-3-fatty acid intake according to NHANES data (2003)(2004)(2005)(2006)(2007)(2008) (Papanikolaou et al, 2014).…”
Section: Consideration Of Fsmps and Fs In Elder Populationmentioning
confidence: 99%